FINANCIAL PLANNING AND MANAGEMENT FOR VOCATIONAL HIGH SCHOOL STUDENTS - Rudi Santoso; Lilis Binawati (Universitas Airlangga, 2023)
This Financial Planning assistance and training aims to provide knowledge and insight to Darussalam Vocational High School students in financial management. The urgency of this activity is the increasing prevalence of fraudulent investments that require understanding and knowledge of how to manage and plan finances from an early age. The method used in this training focuses on seven stages, namely: determining financial position; set financial goals; make financial planning; simple notes; create a budget; facing credit problems; and make a financial review. Evaluation and assessment use the Pre-Test and Post-Test models with a rating scale from level 1 to level 10. The results of the training show a quantitative increase from an average level 4 to an average level 7. A qualitative increase is an average of 50 %. The limitation of this training lies in the relatively short duration of time. This training and assistance can be further developed to become more complex with a longer duration of time so that the results are more optimal.